Les recherches du CIPEA en 1980 - International Livestock Centre for Africa (1981)
Presents and discusses ILCA's research on smallholder farming in the highlands, village sheep and goat production in the humid zone, cattle production in the subhumid zone, pastoral production in the arid zones of West Africa, range livestock production in eastern and southern Africa, and breed evaluation and herd modelling.